Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Kesehatan Provinsi Sumatera Utara - Salman Farisi; Ririn Ulba Utari (Fisarrearch, 2020)
The purpose of this study was to determine the effect of work stress on employee performance, to determine the effect of the work environment on employee performance, and to determine the effect of work stress and work environment on employee performance at the North Sumatra provincial health office. This study uses the theory of human resource management related to work stress, work environment, and employee performance. The approach used in this research is an associative and quantitative approach. The population in this study was 860, while the samples calculated using the Slovin formula totaled 90 people. Data collection techniques in this study used a questionnaire technique. Data analysis techniques in this study used Multiple Linear Regression Test, Classical Assumption Test, Hypothesis Test (T Test and F Test), and the Coefficient of Determination. Data processing in this study uses SPSS software program version 22. Partially known that Job Stress has an influence on employee performance at the Health Office of North Sumatra Province. Partially known that the work environment has an influence on the performance of employees at the North Sumatra Provincial Health Office. Simultaneously it is known that work stress and work environment